'Sport for Yes'? The role of sporting issues in pro-independence political discourse during the Scottish independence referendum campaign. Issue 3 (3rd July 2017) - Whigham, Stuart; May, Anthony
ABSTRACT: This article critically considers the extent to which sporting issues were harnessed by pro-independence political campaigners during the Scottish independence referendum campaign. Developments such as the inclusion of sport within the Scottish Government's White Paper on Scottish independence, the establishment of the 'Working Group on Scottish Sport' and the establishment of the 'Sport for Yes' campaign group demonstrate the harnessing of sporting issues as an additional, if somewhat peripheral, debate point in the referendum campaigns . The latter of these developments, the establishment of the 'Sport for Yes' campaign group, is of particular interest, offering evidence of the explicit political mobilisation of past and present athletes in support of the 'Yes Scotland' pro-independence campaign. The use of sport within pro-independence political discourse is therefore scrutinised, drawing upon the principles of critical discourse analysis to explore the ideological assumptions underpinning the discursive representation of sport in relation to Scottish independence.